Avaliação de eletrodos compósitos de MnO2 e carbono ativado para aplicação em supercapacitores - Feliciano, Anderson Silva (2022)
Evaluation of composite Mno2 and activated carbon electrodes for application in supercapacitors. Manganese dioxide (MnO2) nanoparticles were synthesized by microwave-assisted hydrothermal methodology and characterized by X-ray diffraction (XRD). The composite materials were obtained by mixing different mass fractions of MnO2 (50 – 95%) and CAP (0 – 45%) and a constant fraction of 5% of polyvinylidene (PVDF) as binder. The electrodes produced from different composite materials were analyzed by cyclic voltammetry (VC). The results achieved by charging and discharging (C/D) showed that the composite electrode consisting of 75% (m/m) of MnO2, 20% (m/m) of CAP and 5% (m/m) of PVDF presented a specific capacitance value of 213 F g–1. N2 physisorption and scanning electron microscopy (SEM) analyzes were then performed for the composite material of this electrode (517 m2 g–1) and its precursors (131 m2 g–1 for MnO2 and 2391 m2 g–1 for CAP). Despite the drastic decrease in the specific surface area of the composite material in relation to that of the CAP (~78 %), the electrochemical characterizations showed that there was a synergistic effect when mixing MnO2 and CAP, since the composite electrode exhibited a specific capacitance higher than that of the electrodes produced with precursor materials. C/D tests performed with the best composite electrode at a specific current of 0.2 A g–1 indicated a maximum specific capacitance value of 213 F g–1, decreasing to 170 F g–1 with an ohmic drop of 32 mV when raising the specific current to 2.0 A g–1. Finally, the composite electrode showed charge retention of 77% and coulombic efficiency of 100% after 5000 C/D cycles. Thus, the analyses carried out in this work demonstrate that the composite material consisting of nanometric MnO2 and CAP is a suitable material for application in electrodes of electrochemical capacitors.